Ta thấy \(\left|2x-27\right|\ge0\Rightarrow\left|2x-27\right|^{2011}\ge0\)với mọi x
\(\left(3y+10\right)^{2012}\ge0\)với mọi y
Suy ra \( \left|2x-27\right|^{2011}+\left(3y+10\right)^{2012}\ge0\)với mọi x,y
Mà \( \left|2x-27\right|^{2011}+\left(3y+10\right)^{2012}=0\)
Khi đó \(\hept{\begin{cases}2x-27=0\\3y+10=0\end{cases}\Rightarrow\hept{\begin{cases}x=\frac{27}{2}\\y=-\frac{10}{3}\end{cases}}}\)
Vậy.....
Ta có : \(\hept{\begin{cases}\left|2x-27\right|^{2011}\ge0\\\left(3y+10\right)^{2012}\ge0\end{cases}\Rightarrow\left|2x-27\right|^{2011}+\left(3y+10\right)^{2012}\ge0}\)
Mà \(\left|2x-27\right|^{2011}+\left(3y+10\right)^{2012}=0\)
\(\Leftrightarrow\hept{\begin{cases}2x-27=0\\3y+10=0\end{cases}\Leftrightarrow\hept{\begin{cases}2x=27\\3y=-10\end{cases}\Leftrightarrow}\hept{\begin{cases}x=\frac{27}{2}\\y=\frac{-10}{3}\end{cases}}}\)
và
+)
+)
Vậy